Financial Analysis of a Rice Transplanter Usage in Farming Activity at the Junrejo District in Batu City - Lazuardy Tembang Smaradhana; Sandra Sandra; Gunomo Djoyowasito (Sekolah Pascasarjana Universitas Brawijaya, 2019)
The rice transplanter machine is required to overcome the scarcity of agricultural workers particularly for labor of rice planting. The rice transplanter itself is a machine used to plant rice seedlings into a paddy field. The usage of rice transplanter in farming activity is necessarily studied for financial feasibility, whether it can affect or not an increasement of farmer income. The method that used in this research is financial analysis includes basic costs, feasibility of farming activity which involves net present value (NPV), internal rate of return (IRR), net benefit cost ratio (net B/C Ratio), and payback period (PBP), afterward sensitivity analysis is committed. Data collection is conducted both in primary and secondary such as an interview stage to farmers and several another sources which relevance to the research. This research has conducted an observation towards farming activity at the Junrejo district in Batu City. The outcome of the research shows that the usage of rice transplanter can be said to be feasible at the Junrejo district in Batu City based on the basic costs Rp. 290,700,-/ha, NPV Rp. 65,797,914 IRR 45.29%, Net B/C ratio 2.02 and PBP 2.22 years. The usage of rice transplanter is sensitive to the decline in selling prices by 18% and decrease in production by 15%.